Binding deficits in memory following medial temporal lobe damage in patients with voltage-gated potassium channel complex antibody-associated limbic encephalitis. - Pertzov, Y; Miller, T; Gorgoraptis, N; Caine, D; Schott, J; Butler, C; Husain, M (2013)
Some prominent studies have claimed that the medial temporal lobe is not involved in retention of information over brief intervals of just a few seconds. However, in the last decade several investigations have reported that patients with medial temporal lobe damage exhibit an abnormally large number of errors when required to remember visual information over brief intervals. But the nature of the deficit and the type of error associated with medial temporal lobe lesions remains to be fully established. Voltage-gated potassium channel complex antibody-associated limbic encephalitis has recently been recognized as a form of treatable autoimmune encephalitis, frequently associated with imaging changes in the medial temporal lobe. Here, we tested a group of these patients using two newly developed visual short-term memory tasks with a sensitive, continuous measure of report. These tests enabled us to study the nature of reporting errors, rather than only their frequency. On both paradigms, voltage-gated potassium channel complex antibody patients exhibited larger errors specifically when several items had to be remembered, but not for a single item. Crucially, their errors were strongly associated with an increased tendency to report the property of the wrong item stored in memory, rather than simple degradation of memory precision. Thus, memory for isolated aspects of items was normal, but patients were impaired at binding together the different properties belonging to an item, e.g. spatial location and object identity, or colour and orientation. This occurred regardless of whether objects were shown simultaneously or sequentially. Binding errors support the view that the medial temporal lobe is involved in linking together different types of information, potentially represented in different parts of the brain, regardless of memory duration. Our novel behavioural measures also have the potential to assist in monitoring response to treatment in patients with memory disorders, such as those with voltage-gated potassium channel complex antibody limbic encephalitis.